Opioid Overdose—the Surgeon's Role. Issue 1 (July 2018) - Vu, Joceline V.; Lin, Lewei A.
Abstract : N/A: With increased focus on the potential harms of surgical opioid prescribing, surgeons should be cognizant of the risk of opioid-related adverse events in their patients, including overdose. Risk factors for overdose may be more prevalent than surgeons think, and include high current opioid use, previous or existing substance use disorder, history of overdose, or certain medical comorbidities. The first step to protecting surgical patients from opioid overdose is adequate screening for risk factors; appropriate patient counseling and prudent prescribing practices can then help protect at-risk patients.